A rare simultaneous coexistence of epithelioid gastrointestinal stromal tumors and schwannoma in the stomach: a case report - Yuxin Li; Yongliang Teng; Xiaofei Wei; Zhuang Tian; Yuqing Cao; Xiaona Liu; Xiumei Duan (BMC, 2019)
Abstract Background Gastrointestinal stromal tumors (GISTs), a type of mesenchymal tumor in the gastrointestinal tract, are believed to be closely associated with PDGFRA and C-KIT mutations. Schwannoma in the stomach, which is an unusual location, is a rare disorder. The simultaneous occurrence of the two diseases is rarer than metachronous occurrences, and its pathological characteristics have not been reported to date. We present a case report on a patient with simultaneous coexistence of gastric schwannoma and GISTs. Case presentation A 39-year-old female visited our hospital complaining of intermittent abdominal pain for the previous 3 months. CT revealed a 3.4 cm slight homogeneous enhancement in the lesser curvature of the stomach; the mass was nodular soft tissue, which was removed by radical surgery. Two solid tumors with different volumes were located in the stomach. Histologically and immunohistochemically different, the larger tumor consisted of spindle cells surrounded by a peripheral lymphoid cuff, and was positive for S-100. The larger tumor was therefore classified as a gastric schwannoma. The smaller tumor was composed of medium-sized round, oval cells with amphiphilic granular cytoplasm; vacuolization was also observed. The tumor cells were positive for DOG1 and sporadically positive for CD34 and CD117. Hence, the smaller tumor was diagnosed as epithelioid GISTs. Sanger sequencing revealed that the GIST tumor cells contained a deletion mutation (c.2527_2538 del12,843-846del4), which was located in exon 18 of PDGFRA. Conclusion GISTs combined with gastric schwannoma are a considerably rare subgroup of gastric tumors. Related clinical research is comparatively weak, and the mechanism remains unknown. We reviewed related articles to provide knowledge to improve the correct identification, diagnosis and management of patients with gastric cancer. All pathologists involved in the diagnosis and clinicians involved in the treatment should be aware of this new kind of disease pattern to improve their understanding of the disease.